2021
DOI: 10.3389/fpsyt.2021.642618
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Self-Stigma of Syrian Refugees With Posttraumatic Stress Symptoms: Investigating Sociodemographic and Psychopathological Correlates

Abstract: Background: The high prevalence of mental disorders related to posttraumatic stress among Syrian refugees is often in contrast with their low utilization of mental health care in the host countries. Mental health self-stigma, i.e., internalized stigma of having a mental disorder, could prevent individuals from seeking mental health care. Therefore, we aimed to provide evidence on different aspects of mental health self-stigmatization among adult Syrian refugees with posttraumatic stress symptoms residing in Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…Moreover, the majority of participants came from Syria (53.7%) and were male (72.4%). This distribution is similar to the general population of forcibly displaced people in Germany and common for current samples in this research area (Bär et al, 2021 ; Lindheimer et al, 2020 ). Even though, in the present sample and previous research (Livingston & Boyd, 2010 ), no gender differences in self-stigma were found, gender differences in help seeking are a common finding (Maguen et al, 2012 ; Marshall et al, 2006 ).…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the majority of participants came from Syria (53.7%) and were male (72.4%). This distribution is similar to the general population of forcibly displaced people in Germany and common for current samples in this research area (Bär et al, 2021 ; Lindheimer et al, 2020 ). Even though, in the present sample and previous research (Livingston & Boyd, 2010 ), no gender differences in self-stigma were found, gender differences in help seeking are a common finding (Maguen et al, 2012 ; Marshall et al, 2006 ).…”
Section: Discussionsupporting
confidence: 83%
“…In each result, we attempted to investigated enough similar papers with close questionnaires, and discussed the similarities and the differences. However, we did not discuss studies that involved Syrians in asylum countries [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the perceived stigma subscales, respondents were asked their beliefs about most of the other people’s attitudes toward people with depression symptoms described in the vignette (e.g., “Most people believe that people with depression could snap out of it if they wanted”). The response of each item was measured on a five-point scale ranging from “strongly agree” to “strongly disagree” [ 32 ]. The Chinese version of the scale has been widely used with good reliability and validity [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toward the end of the study, it was concluded that since these students were highly-aware of the dynamics of both these illnesses, they had significantly lower personal stigmas for either of these conditions. Overall, this study helped promote that increased planned campaigning toward reducing stigmas plays a more significant role in eliminating the presence of social stigmas regarding these mental health disorders ( 37 ). Stigmas have always posed significant challenges and risks to the population that is considered the target audience here: people suffering from GAD.…”
Section: Discussionmentioning
confidence: 93%